MHD effects on forced-convection stagnation nanofluid flow over a stretched surface in the presence of heat source/sink using similarity transformation - Mohammed, Ahmed Hasan (2016)
The Magnetohydrodynamics (MHD) effects on forced-convection stagnation flow of Alumina-water (Al2O3-water), Copper-water (Cu-water) and Single Walled Carbon NAnotubes-water (SWCNTs-water) nanofluids over a stretched surface in the presence of heat source/sink is studied that includes consideration of thermal radiation. The governing equations (non-linear PDEs) of continuity, momentum, and energy are transformed into first order ordinary differential equations analytically using similarity transformation. The obtained governing equations have been solved numerically by using fourth or fifth-order Runge-Kutta Fehlberg method with shooting technique. The independent software in this thesis is MAPLE 18 programming, which is used to analysis the set of equations and gets results in plot form. The influence on velocity and temperature is discussed for significant parameters such as the magnetic parameter (M), radiation parameter (Rd), volume friction of nanofluid (y), velocity ratio parameter (λ), and temperature index parameter (n) of the flow and heat transfer characteristics. Salient features of the results are analyzed and discussed.